Feminine Metaphors and Archipelagic Ecological Narratives in Contemporary Indonesian Short Stories - Muhammad Hafidz Assalam; Wening Udasmoro; Aprinus Salam; Wahyu Wiji Astuti; Deswandito Dwi Saptanto (Tabasa: Jurnal Bahasa, Sastra Indonesia, dan Pengajarannya, 2026)
This study aims to explore recent Indonesian short stories written by women in their efforts to produce feminine metaphors as a form of resistance against the singular truth of masculinity. In narrating their short stories, female writers produce feminine metaphors shaped by the ecological conditions surrounding them. These feminine narratives are presented as an accentuation of women's defense against the ecological damage suffered by islands inhabited by humans. The patriarchal system combined with greedy capitalism and modernism has damaged the ecology of the islands where humans live. Through literary works, women carry out symbolic resistance by producing new metaphors as a representation of the mainstreaming of women in their involvement in creating an egalitarian relationship between humans and nature. This study uses the narrative theory approach from Helene Cixous which was then developed into feminine metaphors by Leslie Rabine. Based on an exploratory analysis of linguistic data in the short stories Mandi Mayah and Kesaksian di Titik Didih by Deasy Tirayoh, and Angin Berkabar Hujan by Dian Nangin, the results show that feminine metaphors are closely related to the ecological elements of the islands, including the sea, plantations, and agriculture. In this case, the sea, plantations, and agriculture are combined with efforts to resist patriarchy, capitalism, and modernism through the accentuation of symbolic and metaphorical language. Penelitian ini bertujuan untuk mengeksplorasi cerita pendek Indonesia mutakhir yang ditulis oleh perempuan dalam upaya untuk menghasilkan metafora feminin sebagai bentuk perlawanan terhadap kebenaran tunggal maskulinitas. Dalam menarasikan cerpennya, penulis perempuan menghasilkan metafora feminin yang dibentuk dari kondisi ekologis di sekitar penulis sendiri. Narasi feminin ini disajikan sebagai penekanan pada pembelaan perempuan terhadap kerusakan ekologis yang diderita oleh pulau-pulau yang dihuni manusia. Sistem patriarki yang dikombinasikan dengan kapitalisme yang serakah dan modernisme telah merusak ekologi pulau-pulau tempat manusia tinggal. Melalui karya sastra, perempuan melakukan perlawanan simbolis dengan menghasilkan metafora baru sebagai representasi dari pengarusutamaan perempuan dalam keterlibatannya dalam menciptakan hubungan egaliter antara manusia dan alam. Penelitian ini menggunakan pendekatan teori naratif dari Helene Cixous yang kemudian dikembangkan menjadi metafora feminin oleh Leslie Rabine. Berdasarkan analisis eksploratif data linguistik dalam cerita pendek Mandi Mayah dan Kesaksian di Titik Didih karya Deasy Tirayoh, dan Angin Berkabar Hujan karya Dian Nangin, hasil analis menunjukkan bahwa metafora feminin sangat terkait dengan unsur-unsur ekologis pulau, termasuk laut, perkebunan, dan pertanian. Dalam hal ini, laut, perkebunan, dan pertanian dikorelasikan dengan upaya untuk melawan patriarki, kapitalisme, dan modernisme melalui penekanan pada bahasa simbolis dan metaforis.